Hubungan Frekuensi Hemodialisa Dengan Kejadian Komplikasi Gagal Ginjal Kronik Pada Pasien Yang Sedang Menjalani Hemodialisa Di Indonesia Kidney Care Club (IKCC) - Vabella Wditiar (2020)
Chronic Kidney Failure Disease (CKD) can also be called a decrease in kidney function, if kidney function has decreased all due to appear sepetti, the process of metabolic waste and accumulation of fluids in the body and can cause disturbances in bodily functions that can lead to complications namely cardiovascular disease, fluid buildup, anemia, hypocalcemia, hypersphosphatemia, and impotence (impotence). The relationship between the frequency of hemodialysis with the incidence of complications in patients with chronic ginjl failure is not known with certainty. Therefore researchers are interested in conducting research "The Relationship of Hemodialysis Frequency with Chronic Kidney Failure Incident in Patients Undergoing Hemodialysis in the Indonesian Community of Kidney Care Club". In this study, researchers used a Cross Sectional research design conducted on 65 samples through consecutive sampling. Data collection uses questionnaires and observational sheets which are distributed via Google form. The results of the study are, there is a relationship between the frequency of hemodialysis with the occurrence of complications of chronic kidney failure (anemia, hypocalcemia, hyperphosphatemia, and impotence) in patients undergoing hemodialysis, and there is no relationship between the frequency of hemodialysis with the occurrence of complications of chronic kidney failure (cardiovascular disease) and fluid buildup) in patients undergoing hemodialysis.